Komunikasi Budaya Kesenian Tari Keling Guno Joyo di Desa Singgahan Kecamatan Pulung Kabupaten Ponorogo - Tsalits Maratun Nafiah (Jurnal Ilmu Komunikasi, 2019)
The art of Keling Guno Joyo Dance is one of the regional dances that still exists and is developed by local residents. This article discusses how cultural communication is displayed in the Keling Guno Joyo Dance art at Dukuh Mojo, Singgahan Village, Pulung District, Ponorogo Regency. This research uses a qualitative-descriptive approach. The research data were analyzed by using Miles and Huberman’s descriptive analysis model based on the theory of perception. The result of this research is that cultural communication in the performance of the Keling Guno Joyo Dance is carried out by means of verbal and non-verbal communication, namely through candra, tembang, and rivet songs, and gamelan musical instruments that accompany the dance. In the dance performance, there is a message that is conveyed so that the art of Keling Dance can be used as a traditional communication medium.